Measles transmission in health care waiting rooms: implications for public health response - Hope, Kirsty (World Health Organization, 2012)
BACKGROUND: Seventeen cases of locally acquired measles occurred in South Western Sydney and Sydney local health districts between July and October 2011. Three of the cases were known to have at least one dose of measles-mumps-rubella (MMR) vaccine. Seven cases were infected within a health care setting waiting room by five index cases. Current national protocols require follow-up of all susceptible contacts in the same waiting room for any length of time for up to two hours after the index case has left. METHODS: Cases were interviewed using a standardized questionnaire. Information included: demographics, illness and activities during the exposure and infectious periods. Health care settings provided arrival and discharge times, maps of floor layouts and location of patients during stay. RESULTS: All health care setting transmission occurred in cases who were present at the same time as their index cases, with crossover time ranging from 20 to 254 minutes. No index case was isolated. Index cases were between day four and six of illness when transmission occurred. None of the five index cases and one of seven secondary cases had received at least one dose of MMR vaccine. Of the seven secondary cases, two were one year of age, one was 17 years old and four were between 30 and 39 years old. CONCLUSION: As Australia moves towards measles elimination, follow-up of cases is important; however, with limited public health resources a targeted response is vital. In this small but well documented series of secondary cases acquired in a health care setting, all were infected following direct, proximate contact of at least 20 minutes. Changes to the national guidelines may be warranted, ensuring that limited resources are focused on following up contacts at greatest risk of disease.